(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This article examines the observance of technical safety rules during training and competitions by athletes engaged in the sport of table tennis, as well as the causes of sports injuries, data aimed at injury prevention and their analysis. In addition, there is a lot of necessary information related to these processes.